Resource Conflict in Indonesia in a Global Security Perspective: Asymmetric Warfare Study - Rachmawati, Dewi Tiur; Timur, Fauzia Gustarina Cempaka; Widodo, Pujo (PT FORMOSA CENDEKIA GLOBAL, 2024)
Resource conflicts in Indonesia have been going on for a long time, especially regarding land ownership and natural resources such as gold, nickel, oil and gas and others. This conflict involves the state, companies and indigenous communities. One example is the conflict between Freeport and the Papuan people regarding gold mining there. These conflicts can be analyzed using Resource Warfare, Asymmetric Warfare, and State Defense theories. The aim of this research is to analyze resource conflicts in Indonesia using these theories, as well as looking at the role of resources in winning asymmetric wars. This research uses qualitative methods by conducting a literature review of the theories of Resource Warfare, Asymmetric Warfare, and State Defense, as well as case studies of resource conflicts in Indonesia such as Freeport in Papua, Newmont in Sulawesi, and Pongkor in West Java. Data was collected from various references and then analyzed descriptively. The results of the analysis show that resource conflicts in Indonesia can be understood through Resource Warfare and Asymmetric Warfare theories. Countries, companies and indigenous communities compete for resources for their respective interests. In an asymmetric war, possession of resources such as gold and nickel becomes important to win the war. Meanwhile, State Defense theory explains the state's efforts to defend its sovereignty and security regarding this resource conflict.